CO2 Absorption Kinetics of Micro-encapsulated Ionic Liquids. (July 2017) - Stolaroff, Joshuah K.; Ye, Congwang; Nguyen, Du T.; Oakdale, James; Knipe, Jennifer M.; Baker, Sarah E.
Abstract: For widespread adoption of carbon capture and storage to fight climate change, major reductions in both the energy use and capital cost of carbon capture are needed. Many purpose-designed, water-lean solvents have recently been developed to improve the energy-efficiency of carbon capture. These solvents, including ionic liquids (ILs), have shown promise for substantially lower energy demand in post-combustion capture but have drawbacks like high viscosity and solid precipitates. Micro-encapsulation is a technique where a solvent is encased in small (∼500 μm diameter), spherical shells of a CO2 -permeable polymer, greatly increasing the reactive surface area of the solvent and safely containing solid precipitates. Here, we show the kinetics of an IL are enhanced by microencapsulation. The kinetics of the IL in liquid and encapsulated form are compared with those for sodium carbonate solution and the cases where the capsule shell material limits mass transfer are identified. Finally, we make the first demonstration of microencapsulated CO2 solvents in a flow-through, fixed bed reactor. CO2 absorption rates are broadly in agreement with static CO2 absorption measurements made previously.